Pemenuhan Asas Keadilan dalam Pemberian Ganti Kerugian Terhadap Pemilik Tanah Akibat Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Bastanta, Ali; Herning Sitabuana, Tundjung (LPPM Universitas Ekasakti Padang, 2024)
In the practice of land acquisition for development in the public interest, affected land owners must be given appropriate compensation and fulfill the principles of justice. In the end, often providing compensation for these losses is not appropriate and fair. This research aims to reveal justice in providing compensation to land owners due to land acquisition for development in the public interest. This study is a normative legal study which has descriptive characteristics. Secondary data which includes primary, secondary and tertiary legal material was obtained through library study. After the data is collected, it is then studied using qualitative analysis techniques based on a statutory approach. The findings of this research show that providing compensation to land owners due to land acquisition for development in the public interest is often because justice is not met.